Orbital forcing of the marine isotope stage 9 interglacial. - Stirling, C; Esat, T; Lambeck, K; McCulloch, M; Blake, S; Lee, D; Halliday, A (2001)
Milankovitch orbital forcing theory has been used to assign time scales to many paleoclimate records. However, the validity of this theory remains uncertain, and independent sea-level chronologies used to test its applicability have been restricted largely to the past approximately 135,000 years. Here, we report U-series ages for coral reefs formed on Henderson Island during sea-level high-stands occurring at approximately 630,000 and approximately 330,000 years ago. These data are consistent with the hypothesis that interglacial climates are forced by Northern Hemisphere summer solar insolation centered at 65 degrees N latitude, as predicted by Milankovitch theory.